Remittances and Child Labour in Africa: Evidence from Burkina Faso - Delphine Boutin (Institute for the Study of Labor (IZA), 2014)
This paper explores the effects of remittance receipt on child labour in an African context. We focus on Burkina Faso, a country with a high prevalence of child labour and a high rate of migration. Given the complex relationship between remittance receipt and child labour, our identification relies on different instruments capturing the employment conditions in remittance-sending countries. We first find that receiving remittances has no significant effect on child labour on average. However, when the disruptive effect from the absence of a family member is ruled out, remittances significantly reduce child labour. We provide an extensive robustness check and estimate heterogeneous effects. These show no gender difference but a significant age effect: remittances affect the labour market participation of younger children only, suggesting a progressive integration of children into work activities.
Keywords: F24; I25; J22; 330; child labour; migration; Africa; remittances